Association Between Cervical Radiculopathy, Resilience, Perceived Stress And Quality Of Life In IT Professional - R Deepak; Arpit; A. Tanvi (Revista Electronica de Veterinaria, 2024)
Background: Cervical radiculopathy (CR) is a common condition among IT professionals due to prolonged desk work, poor ergonomics, and repetitive stress. The relationship between resilience, perceived stress, and quality of life (QoL) in individuals with CR remains underexplored. Objective: To investigate the association between resilience, perceived stress, and QoL in IT professionals with CR. Methods: A cross-sectional study was conducted among IT professionals aged 25-45 years diagnosed with CR. Resilience was assessed using the Connor-Davidson Resilience Scale (CD-RISC), perceived stress using the Perceived Stress Scale (PSS), and QoL using the WHOQOL-BREF. Data were analyzed using Pearson’s correlation and regression analysis to determine associations. Results: Resilience was negatively correlated with perceived stress (r = -0.56, p < 0.01) and positively correlated with QoL domains (physical: r = 0.48, psychological: r = 0.52, p < 0.01). Higher perceived stress was associated with lower QoL scores (r = -0.62, p < 0.01). Regression analysis indicated that resilience significantly predicted better QoL (β = 0.42, p < 0.01) while perceived stress negatively impacted QoL (β = -0.47, p < 0.01). Conclusion: Resilience and perceived stress play crucial roles in influencing QoL in IT professionals with CR. Interventions to enhance resilience and reduce stress could improve QoL in this population.